2011
DOI: 10.1128/cvi.00314-10
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Protective Haemophilus parasuis Subunit Vaccines Based on Native Proteins with Affinity to Porcine Transferrin and Comparison with Other Subunit and Commercial Vaccines

Abstract: Haemophilus parasuis is the agent responsible for causing Glässer's disease, which is characterized by fibrinous polyserositis, polyarthritis, and meningitis in pigs. In this study, we have characterized native outer membrane proteins with affinity to porcine transferrin (NPAPT) from H. parasuis serovar 5, Nagasaki strain. This pool of proteins was used as antigen to developed two vaccine formulations: one was adjuvanted with a mineral oil (Montanide IMS 2215 VG PR), while the other was potentiated with a bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
36
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 39 publications
10
36
1
2
Order By: Relevance
“…One study showed that a TbpA fragment from H. parasuis serovar 5 can induce an immunological response and might be useful as an antigen for a vaccine. Furthermore, the rTbpA fragment (38.5 kDa, corresponding to 200 amino acids) showed significant bactericidal activity but very poor protection partly because of the reduced length of the tpbA gene fragment (10,28). A previous study in our laboratory showed that three fragments of the rTbpA1, rTbpA2, and rTbpA3 proteins with sizes of 62, 54, and 44 kDa were successfully expressed in E. coli.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One study showed that a TbpA fragment from H. parasuis serovar 5 can induce an immunological response and might be useful as an antigen for a vaccine. Furthermore, the rTbpA fragment (38.5 kDa, corresponding to 200 amino acids) showed significant bactericidal activity but very poor protection partly because of the reduced length of the tpbA gene fragment (10,28). A previous study in our laboratory showed that three fragments of the rTbpA1, rTbpA2, and rTbpA3 proteins with sizes of 62, 54, and 44 kDa were successfully expressed in E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…In H. parasuis, the expression of the tbpB gene has been reported. Unfortunately, the rTbpB protein gave no protection in piglets (10,24,25 useful as a candidate target for H. parasuis vaccination. One study showed that a TbpA fragment from H. parasuis serovar 5 can induce an immunological response and might be useful as an antigen for a vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to compare the immunogenicity of the H. parasuis Hp5 wild-type and Y167A mutant TbpBs, an immunization and challenge experiment was implemented similar to those performed previously (24). Groups of pigs were immunized with PBS (control group, 5 pigs), a commercial vaccine (PorcillisGlässer group, 5 pigs), the wild-type TbpB (native TbpB group, 6 pigs), or the Y167A mutant TbpB (mutant TbpB group, 6 pigs).…”
Section: Generating Tf Binding Mutants Of Tbpb With Minimal Structuramentioning
confidence: 99%
“…None of the studies with other human pathogens (19,22,23) have extended to further trials in humans, and thus they have not provided further insights into the performance of intact TbpB antigens in the natural host. Studies evaluating the potential of Tf receptor based vaccines in food production animals (20,21,24) were performed directly in the natural host and thus did not lead to questions regarding their relative performance in the natural and heterologous host.…”
mentioning
confidence: 99%